Prophylactic intravenous magnesium sulfate for treatment of aneurysmal subarachnoid hemorrhage: A randomized, placebo-controlled, clinical study* - Westermaier, Thomas L.; Stetter, Christian; Vince, Giles H.; Pham, Mirko; Tejon, Jose Perez; Eriskat, Jörg; Kunze, Ekkehard; Matthies, Cordula; Ernestus, Ralf-Ingo; Solymosi, Laszlo; Roosen, Klaus (Critical care medicine, 2010)
Objective: - To examine whether the maintenance of elevated magnesium serum concentrations by intravenous administration of magnesium sulfate can reduce the occurrence of cerebral ischemic events after aneurysmal subarachnoid hemorrhage. - Design: - Prospective, randomized, placebo-controlled study. - Setting: - Neurosurgical intensive care unit of a University hospital. - Interventions: - One hundred ten patients were randomized to receive intravenous magnesium sulfate or to serve as controls. Magnesium treatment was started with a bolus of 16 mmol, followed by continuous infusion of 8 mmol/hr. Serum concentrations were measured every 8 hrs, and infusion rates were adjusted to maintain target levels of 2.0-2.5 mmol/L. Intravenous administration was continued for 10 days or until signs of vasospasm had resolved. Thereafter, magnesium was administered orally and tapered over 12 days. - Measurements and Main Results: - Delayed ischemic infarction (primary end point) was assessed by analyzing serial computed tomography scans. Transcranial Doppler sonography and digital subtraction angiography were used to detect vasospasm. Delayed ischemic neurologic deficit was determined by continuous detailed neurologic examinations; clinical outcome after 6 months was assessed using the Glasgow outcome scale. Good outcome was defined as Glasgow outcome scale score 4 and 5. - The incidence of delayed ischemic infarction was significantly lower in magnesium-treated patients (22% vs. 51%; p = .002); 34 of 54 magnesium patients and 27 of 53 control patients reached good outcome (p = .209). Delayed ischemic neurologic deficit was nonsignificantly reduced (9 of 54 vs. 15 of 53 patients; p = .149) and transcranial Doppler-detected/angiographic vasospasm was significantly reduced in the magnesium group (36 of 54 vs. 45 of 53 patients; p = .028). Fewer patients with signs of vasospasm had delayed cerebral infarction. - Conclusion: - These data indicate that high-dose intravenous magnesium can reduce cerebral ischemic events after aneurysmal subarachnoid hemorrhage by attenuating vasospasm and increasing the ischemic tolerance during critical hypoperfusion.